Pathogenicity of biological formulations based on Beauveria peruviensis and Metarhizium sp. under controlled conditions and their efficacy in the field for the control of coffee berry borer in Peru - Lily Juarez-Contreras; Jesús Rascón; Carlos Oliva-Cruz; Carmen N. Vigo; Carlos Santa Cruz; Lorenzo Culqui; Manuel Oliva-Cruz (Journal of Agriculture and Food Research)
The objective was to evaluate the pathogenicity and efficacy of biological formulations based on Beauveria peruviensis and Metarhizium sp. to control the coffee berry borer (Hypothenemus hampei). Pathogenicity, understood as the capacity of the fungal strains to cause mortality and expressed as a percentage of dead insects, was evaluated in the laboratory using 18 treatments, which resulted from combinations of two strains of B. peruviensis (P4 and P19), three strains of Metarhizium sp. (TOR-M16, MMR-M1 and MMR-M15) and three concentrations (1 x 106, 1 x 107 and 1 x 108 conidia/mL). Then, six treatments with higher pathogenicity and ease of reproduction were selected for the field trials, in which the efficacy of the formulations, incidence of H. hampei, and physical yield of the coffee were evaluated. Variables such as temperature, evapotranspiration, precipitation, hours of sunshine, and relative humidity were recorded throughout the field trial. In the laboratory, most treatments exceeded 70 % pathogenicity, and four reached 100 %. In field evaluations, treatment 4 (TOR-M16 + P4 at 1x107) stood out considerably, with 100 % efficacy in the last evaluation. In addition, it was observed that evapotranspiration presented an inverse correlation with incidence and a direct correlation with the efficacy of the biological formulation. The results suggest that the biological formulation of treatment 4 offers effective control of coffee berry borer and that evapotranspiration is an important factor in optimizing the performance of biological formulations in the field.